miR-202-3p Regulates Sertoli Cell Proliferation, Synthesis Function, and Apoptosis by Targeting LRP6 and Cyclin D1 of Wnt/β-Catenin Signaling - Chao Yang; Chencheng Yao; Ruhui Tian; Zijue Zhu; Liangyu Zhao; Peng Li; Huixing Chen; Yuhua Huang; Erlei Zhi; Yuehua Gong; Yunjing Xue; Hong Wang; et al. (Elsevier, 2019)
MicroRNAs (miRNAs) play important roles in mammalian spermatogenesis, which is highly dependent on Sertoli cells. However, the functions and mechanisms of miRNAs in regulating human Sertoli cells remain largely unknown. Here, we report that hsa-miR-202-3p mediates the proliferation, apoptosis, and synthesis function of human Sertoli cells. miR-202-3p was upregulated in Sertoli cells of Sertoli cell-only syndrome (SCOS) patients compared with obstructive azoospermia (OA) patients with normal spermatogenesis. Overexpression of miR-202-3p induced Sertoli cell apoptosis and inhibited cell proliferation and synthesis, and the effects were opposite when miR-202-3p was knocked down. Lipoprotein receptor-related protein 6 (LRP6) and Cyclin D1 of the Wnt/β-catenin signaling pathway were identified as direct targets of miR-202-3p in Sertoli cells, which were validated by bioinformatics tools and dual-luciferase reporter assay. Differentially expressed LRP6 and Cyclin D1 between OA and SCOS Sertoli cells were also verified. LRP6 small interfering RNA (siRNA) interference not only mimicked the effects of miR-202-3p overexpression, but also antagonized the effects of miR-202-3p inhibition on Sertoli cells. Collectively, miR-202-3p controls the proliferation, apoptosis, and synthesis function of human Sertoli cells via targeting LRP6 and Cyclin D1 of the Wnt/β-catenin signaling pathway. This study thus provides a novel insight into fate determinations of human Sertoli cells and niche of human testis. Keywords: human Sertoli cells, miR-202-3p, proliferation and apoptosis, synthesis, LRP6, Cyclin D1, Wnt/β-catenin